2020
DOI: 10.3390/molecules25071727
|View full text |Cite
|
Sign up to set email alerts
|

2-Methyloxolane as a Bio-Based Solvent for Green Extraction of Aromas from Hops (Humulus lupulus L.)

Abstract: The potential of using the bio-based solvent 2-methyloxolane, also known as 2-methyltetrahydrofuran or 2-MeTHF, as an alternative to petroleum solvents such as hexane, was investigated for the extraction of volatile compounds from hop cones (Humulus lupulus L.). Lab scale extractions were coupled with in silico prediction of solutes solubility to assess the technical potential of this bio-based solvent. The predictive approach was performed using the simulation software COSMO-RS (conductor like screening model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Predicted solubilities of some selected solutes usually found in soybean oil were determined in 2-MeOx, 2-MeOx 95.5%, and n -hexane, using the conductor-like screening model for real solvents (COSMO-RS). Briefly, COSMO-RS is a calculation method developed by Klamt using a quantum chemistry model, which has been applied since 2000 for solubility prediction in the context of natural products extraction. , More detailed explanations are presented in our previous studies. , Calculations were performed using the COSMOThermX software (Version 18.0.2, COSMOlogic GmbH & Co., Leverkusen, Germany), at 55 °C, using the “iterative” mode, considering that solutes and solvents are pure and in a liquid state.…”
Section: Methodsmentioning
confidence: 99%
“…Predicted solubilities of some selected solutes usually found in soybean oil were determined in 2-MeOx, 2-MeOx 95.5%, and n -hexane, using the conductor-like screening model for real solvents (COSMO-RS). Briefly, COSMO-RS is a calculation method developed by Klamt using a quantum chemistry model, which has been applied since 2000 for solubility prediction in the context of natural products extraction. , More detailed explanations are presented in our previous studies. , Calculations were performed using the COSMOThermX software (Version 18.0.2, COSMOlogic GmbH & Co., Leverkusen, Germany), at 55 °C, using the “iterative” mode, considering that solutes and solvents are pure and in a liquid state.…”
Section: Methodsmentioning
confidence: 99%
“…At optimum conditions, it was found that 2-MeOx outperformed hexane by increasing limonene extraction yield by 40%. The following year, its ability to extract volatile compounds from hop cones was also demonstrated[21]. This time again the aroma yield obtained with 2-MeOx (20.2%) was higher than what was obtained with n-hexane (17.9%) and both extracts had similar compositions and olfactory profiles.2-MeOx appears to be an efficient bio-based solution for preparation of color samples as well, particularly in the case of carotenoids.…”
mentioning
confidence: 90%
“…Hexane is typically one of the main solvents used to recover aromatic compounds from natural products. Considering its hazardous characteristic to human health and environment, a lot of efforts are made to find a suitable alternative applicable in the industry [ 30 , 31 , 39 , 40 ].…”
Section: 2-methyloxolane As Extraction Solvent For Production Of Nmentioning
confidence: 99%
“…The results of this analysis support the suitability of replacing hexane with 2-MeOx to develop sustainable processes. Recently, we investigated the potential of using 2-MeOx for the extraction of volatile compounds from hop cones [ 40 ]. Again, the crude yields provided by 2-MeOx either after maceration or Soxhlet procedure were higher than that of hexane (16.6 and 20.2% against 12.7 and 17.9%).…”
Section: 2-methyloxolane As Extraction Solvent For Production Of Nmentioning
confidence: 99%